Research on long-term stability of coal pillar group in strip mining of inclined coal seam - Yuanfeng CHEN; Jing YANG; Zhanguo MA; Xianbiao MAO (Meikuang Anquan)
In the strip coal mining under buildings, railways and water-bodies and other retaining coal pillar mining methods, the long-term stability of coal pillar group is of paramount importance to the safe and efficient green mining. Based on the interaction relationship between coal pillar and surrounding rock, the plane strain model of retaining coal pillar in inclined coal seam is established, and the analytical expressions of coal pillar stress field and displacement field are deduced by using Rits method. On this basis, combined with the actual strip mining in a certain village, the FLAC3D finite difference numerical simulation method is used to establish a numerical calculation model for the long-term stability of coal pillars in inclined coal seams. Based on Burgers combined creep viscoelastic-plastic constitutive model and numerical simulation results, the effect of time and coal pillar width on long-term stability of coal pillar group is studied. Theoretical and numerical research results show that, affected by the inclination angle of the coal seam, the horizontal displacement of a single coal pillar is more than twice of its vertical displacement. Under the long-term action of the gravity of the overlying strata, the two sides of each coal pillar enters the plastic yielding state after 1 day of creep, and presents a shear failure form. The greater the buried depth of coal pillar, the higher the plastic zone range, stress and displacement peak value of coal pillar at any time, and the time required for coal pillar to reach the stable creep stage gradually increases from 75 days to more than 120 days.